Evaluation of Hospital Infrastructure and Human Resource Readiness for the Implementation of Electronic Medical Records (EMR) Integrated with the SATUSEHAT Platform - Septi Viantri Kurdaningsih; Shelly Rodliah Rosyad; Aisyiyah Hanif Muallim; Hasnawati; Fitriani Abdal (Journal of Health Service Administration and Hospital Management, 2025)
This study evaluated the readiness of 135 Indonesian hospitals (Type B and C) for mandatory EMR integration with the SATUSEHAT platform. Recognizing a critical research gap in evaluating maturity against specific HL7 FHIR interoperability and governance standards, the study utilized a Quantitative Secondary Data-Based Readiness Evaluation Design. Binary Logistic Regression identified the strongest predictors for successful integration. Results indicate that while basic infrastructure is adequate, readiness is hampered by advanced factors. The two most significant predictors were Data Security Certification ( ) and the IT Personnel to Clinical Staff Ratio ( ). This confirms that the primary hurdles are the Interoperability Governance Gap (low security compliance,  ) and the lack of specialized technical human capital. Implications mandate a Targeted Intervention Strategy (TIS): linking digital transformation subsidies to mandatory Data Security Certification compliance and prioritizing the retention of specialized IT talent. Achieving national digital health requires immediate investment in formal data governance and dedicated technical staff.